A Didactic Approach to Writing Skills in a Technical Learning Environment. (2016) - Rus, Dana
Abstract: The present paper is a theoretical approach to the component of English language didactics which deals with the practice of writing skills in the context of an English lesson for engineering students. At the same time, the paper suggests some activities, strategies and methods which a language instructor may use during the class for an adequate achievement of teaching objectives for a lesson focused on the development of writing skills.